Radiographic appearance of ossifying fibroma in the left mandible: a case report - Mahindra Awwaludin Romdlon; Farina Pramanik; Achmad Mauludin (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
This article reports on ossifying fibroma (OF) which was established based on panoramic radiographic, CBCT and histopathological examination and treatment performed on a 31 years old male patient. The diagnosis is made by comparing with existing theories in the literature. Case Report: A 31 years old man was referred to the Oral Surgery Department of Al Ihsan Hospital. The patient complained of swelling in the lower left jaw. On palpation it feels hard and cannot be moved. Panoramic radiograph examination showed loss of teeth 34-35 and a radiolucent lesion mixed with radiopaque in the left mandible which resulted in a shift in the position of teeth 36 and 37 more superiorly. The CBCT examination performed revealed a mixed radiolucent and radiopaque lesion of teeth 33-38. Histopathological examination also showed the presence of cellular fibrous with a mineralized component. The patient has been treated in the form of excision of the lesion. Conclusion: CBCT can be used as a reliable supporting examination in helping to diagnose cases of benign neoplasms involving hard bone tissue such as ossifying fibroma. OF has distinctive features on radiographs, one of which is the presence of mixed radiolucent and radiopaque lesions with wispy septa which result in resorption and displacement of the teeth involved. The accuracy of the diagnosis of OF can be enforced by a combination of clinical, radiographic and HPA examinations, so that the treatment given to patients is according to the procedure.